Relationship economics : transform your most valuable business contacts into personal and professional success - Nour, David, 1968- (John Wiley & Sons, Inc., 2023)
"A revised and updated guide to bridging relationship creation with relationship capitalization Relationship Economics isn't about taking advantage of friends or coworkers to get ahead. It's about prioritizing and maximizing a unique return on strategic relationships to fuel unprecedented growth. Based on the author's global speaking and consulting engagements, Relationship Economics reveals that success comes from investing in people for extraordinary returns. This revised and updated third edition explains the three major types of relationships--personal, functional, and strategic--and how to focus each to fuel enterprise growth. It introduces new concepts in relationship management, including the exchange of Relationship Currency®, the accumulation of Reputation Capital®, and the building of Professional Net Worth®. These are the fundamental measures of business relationship, and once you understand them, you'll be able to turn your contacts into better executions, performance, and results"--